Associations of Maternal Sociodemographic Characteristics and Eating Behaviors with Infant Feeding Behaviors. (29th May 2020) - Nansel, Tonja; Lipsky, Leah; Schwedhelm, Carolina; Wright, Breanne; Temmen, Chelsie; Faith, Myles; Nicholson, Wanda; Siega-Riz, Anna Maria
Abstract: Objectives: This study examines associations of maternal characteristics with infant feeding of discretionary and health-promoting foods. Methods: Mothers in PEAS, a prospective cohort study, reported maternal and child dietary intake, demographics, and eating competence (EC). Maternal diet quality (Healthy Eating Index-2015, HEI) was calculated combining 24-hour diet recalls at 6 weeks, 6, and 12 months postpartum ( n  = 209). Infant food frequency questionnaires were completed at 6, 9, and 12 months, assessing age of introduction and intake frequency of food groups. T-tests examined bivariate associations of demographics with feeding of discretionary sweets, discretionary savory foods, fruit, and vegetables. Linear regressions examined associations of maternal EC and HEI with infant feeding controlling for demographics. Results: Fruit, vegetables, discretionary sweet, and discretionary savory foods were introduced at 5.8 ± 1.7, 5.9 ± 1.7, 8.0 ± 2.0, and 8.8 ± 1.8 months, respectively. Earlier introduction of fruit and vegetables was associated with higher maternal education, white race, and nulliparity; earlier introduction of vegetables was also associated with higher income. Age of introduction of discretionary sweet and savory foods was not associated with maternal demographics, HEI, or EC. At age 12 months, greater infant intake frequency of fruit and vegetables was associated with higher education and income, white race, and breastfeeding, while greater intake frequency of discretionary sweet and savory foods was associated with lower maternal education and minority race. Greater intake frequency of sweets was also associated with multiparity and greater intake frequency of discretionary savory foods was associated with lower income. Maternal HEI was positively associated with infant intake frequency of fruit, vegetables, and discretionary sweet and savory foods. Maternal EC was positively associated with infant intake frequency of fruit and vegetables. Conclusions: Demographic differences in infant feeding behaviors indicates these behaviors as critical intervention targets to address disparities in child diet quality. Associations of maternal HEI and EC with infant feeding behaviors suggest potential pathways of maternal influence on infant diet. Funding Sources: This research was supported by the NICHD Intramural Research Program.